Chimpanzee susceptibility to hepatitis C virus infection correlates with presence of Pt-KIR3DS2 and Pt-KIR2DL9: paired activating and inhibitory natural killer cell receptors - Abi-Rached, Laurent (Immunogenetics, 2015)
Infection of humans and chimpanzees with Hepatitis C virus (HCV) results in either the resolution of the acute infection or its progression to a persistent infection associated with chronic liver disease. In cohorts of human patients, resolution of HCV infection has been associated with homozygosity for both C1(+)HLA-C and its cognate inhibitory receptor, KIR2DL3. Compared here are the killer cell immunoglobulin-like receptors (KIR) and major histocompatibility complex (MHC) class I factors of chimpanzees who resolve, or resist, HCV infection with those chimpanzees who progress to chronic infection. Analysis of Pt-KIR gene content diversity associated two of the 12 Pt-KIR with clinical outcome. Activating Pt-KIR3DS2 and inhibitory Pt-KIR2DL9 are strong receptors specific for the C2 epitope. They are encoded by neighboring genes within the Pt-KIR locus that are in strong linkage disequilibrium. HCV-infected chimpanzees with KIR genotypes containing Pt-KIR3DS2 and KIR2DL9 are significantly more likely to progress to chronic infection than infected chimpanzees lacking the genes (p=0.0123 and p=0.0045, respectively), whereas human HLA-B allotypes having the C1 epitope are unusual, such allotypes comprise about one quarter of the chimpanzee Patr-B allotypes. Homozygous C1-(+)Patr-B are enriched in chimpanzees with chronic HCV infection, and the compound genotype of homozygous C1(+)Patr-B combined with either Pt-KIR3DS2 or Pt-KIR2DL9 is more strongly associated with disease progression than either factor alone (p=0.0031 and p=0.0013, respectively). Thus, despite similarities suggesting a common basis in disease resistance, there are substantial differences in the KIR and MHC class I correlations observed for HCV-infected humans and chimpanzees, consistent with the divergence of their KIR and MHC class I systems.